Clinical Characteristics and Therapeutic Adherence of Women in a Referral Outpatient Clinic for Severe Hypertension - Barletta,Pedro Henrique (2021)
Abstract Background Cardiovascular disease is the main cause of death worldwide. There is a lack of studies addressing this issue in women and its risk factors, such as hypertension. Objective To evaluate the clinical and therapeutic profile of women with hypertension and to determine which factors are related to treatment adherence and blood pressure control. Methods Cross-sectional study of 181 hypertensive women treated at an outpatient referral clinic. Data were obtained from medical records, face-to-face interviews, and physical examination, using a standardized form. Statistical analysis was performed with prevalence ratio, chi-square and Student’s t test. Significance was accepted at p<0.05. Results Most patients were mixed-race or black (91.7%) and the mean age was 66.09 years. Only 44.2% of patients had controlled blood pressure. The prevalence of stroke was 14.9%, whereas the prevalence of coronary artery disease was 19.3%. The mean number of oral antihypertensive drugs prescribed to each individual was 3.41. A history of stroke was more often found in patients with uncontrolled blood pressure (p=0.013) and in those using three or more antihypertensives (p=0.023). Eighty patients (44.2%) had high treatment adherence. Depression was more frequently reported by patients with poorer adherence to treatment (p=0.026). Conclusion Women with hypertension presented a high prevalence of cardiovascular risk factors and cardiovascular events, including a significantly higher prevalence of stroke in those with uncontrolled hypertension. Self-reported depression may help identify patients at risk of nonadherence to treatment.